The CO2CRC Otway shallow CO2 controlled release experiment: Preparation for Phase 2. (November 2018) - Feitz, Andrew; Tertyshnikov, Konstantin; Pevzner, Roman; Ricard, Ludo; Harris, Brett; Schaa, Ralf; Schacht, Ulrike; Kalinowski, Aleks; Vialle, Stephanie; Glubokovskikh, Stanislav; Lebedev, Maxim; Tenthorey, Eric; et al.
Abstract: CO2CRC and its partners are undertaking a feasibility study for a planned CO2 controlled release and monitoring experiment on a shallow fault at the CO2CRC Otway Research Facility. In this project we plan to image, using a diverse range of geophysical and geochemical CO2 monitoring techniques, the migration of CO2 up a fault from a controlled release point at approximately 30 m depth. This paper describes the results of site characterisation and modelling work undertaken to date. It also includes a description of the activities planned that will enable for a more detailed characterization of the fault and proposed injection interval. Together these results will enable an assessment as to whether the planned injection experiment is feasible and how it can be optimally designed.